2011
DOI: 10.1177/0021998311412407
|View full text |Cite
|
Sign up to set email alerts
|

Melt mixed compatibilized polypropylene/clay nanocomposites. II. Dispersion vs. thermal properties, optical transmittance, and fracture behaviors

Abstract: Compatibilized polypropylene (PP)/clay nanocomposites using two different types of maleated compatibilizers, polyolefin elastomer-grafted maleic anhydride (POE- g-MA) and PP-grafted maleic anhydride (PP- g-MA), to improve the dispersion of various amounts of commercial organoclay (Closite 20 A) were prepared via a melt-mixing technique. The optical transmittance for the POE- g-MA compatibilized nanocomposites was lower than that of PP- g-MA compatibilized cases, although POE- g-MA greatly increased the interla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…This could be attributed to the filler–filler interaction of the clay at high filler loadings, hence resulting in agglomerates, and thus intercalation of the polymer melt into interlayer clays became more difficult. 3,16 This finding is consistent with the previous study. 3,6,26 The increased intensity of the (001) peaks at 5 phr MMT seen in Figure 7 indicates that MMT tends to agglomerate or flocculate with increasing concentration of MMT.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This could be attributed to the filler–filler interaction of the clay at high filler loadings, hence resulting in agglomerates, and thus intercalation of the polymer melt into interlayer clays became more difficult. 3,16 This finding is consistent with the previous study. 3,6,26 The increased intensity of the (001) peaks at 5 phr MMT seen in Figure 7 indicates that MMT tends to agglomerate or flocculate with increasing concentration of MMT.…”
Section: Resultssupporting
confidence: 93%
“…3,16 This finding is consistent with the previous study. 3,6,26 The increased intensity of the (001) peaks at 5 phr MMT seen in Figure 7 indicates that MMT tends to agglomerate or flocculate with increasing concentration of MMT. Jiang et al also observed an increase in the intensity at 5 wt% of MMT and larger agglomeration with higher MMT content.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations